2011
DOI: 10.1002/marc.201100514
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of Rod–Coil Polyethylenimine–Poly(ethylene glycol)–α‐Cyclodextrin Inclusion Complexes into Hollow Spheres and Rod‐Like Particles

Abstract: This paper describes the self‐assembly of rod–coil inclusion complexes, polyethylenimine–poly(ethylene glycol)–α‐cyclodextrin (PEI–PEG–α‐CD). It is demonstrated that α‐CDs should exclusively thread on the PEG block in PEI–PEG copolymers and the resulting complexes have both rigid block (PEG–α‐CD) and coil block (protonated PEI). By varying the rigid block fraction, aggregates with hollow spheres or rod‐like particles could be formed simply by self‐assembly in aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Therefore, the WSs@pH4 likely represent a type of wormlike micelles with hollow cavities (bright domains in Figure a–c). This was verified by the significantly smaller height (100–130 nm) than the width (1 μm) in the collapsed state (Figure S3d,h,l Supporting Information), which is generally attributed to a hollow structure as found for similar amphiphilic assemblies . Theoretically, the diameter of WSs@pH4 is much larger than the estimated chain length of extended PAH (95 nm), suggesting a hollow nature as well.…”
Section: Resultssupporting
confidence: 66%
“…Therefore, the WSs@pH4 likely represent a type of wormlike micelles with hollow cavities (bright domains in Figure a–c). This was verified by the significantly smaller height (100–130 nm) than the width (1 μm) in the collapsed state (Figure S3d,h,l Supporting Information), which is generally attributed to a hollow structure as found for similar amphiphilic assemblies . Theoretically, the diameter of WSs@pH4 is much larger than the estimated chain length of extended PAH (95 nm), suggesting a hollow nature as well.…”
Section: Resultssupporting
confidence: 66%
“…Due to the propensity of the rigid blocks to pack in parallel, the rod‐coil complexes formed hollow particles. Varying the rigid block fraction was an effective way to control the morphology of the aggregates . In this study, PEI(10K)‐mPEG/α‐CD had a low rigid block fraction (rod:coil = 1:5) and self‐assembled to spheres, while PEI(2.5K)‐mPEG/α‐CD had a high rigid block fraction (rod:coil = 1:1) and self‐assembled to rod‐like particles.…”
Section: Resultsmentioning
confidence: 78%
“…Our recent research has demonstrated that rod‐coil complexes formed by CD and polymer chains could self‐assemble into hollow spheres or rod‐like tubes in aqueous solution by varying the rigid block length fraction . Earlier research focused on the methodology and control of morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired from nature, some peptides (Block et al, 2005;Scanlon and Aggeli, 2013;Toksöz and Guler, 2009), amphiphilic molecules (Dalhaimer et al, 2004;Israelachvili et al, 1976;Kim et al, 2005), and dendritic molecules (Gillies and Fréchet, 2005;Ihre et al, 2002) have been shown to auto-assemble and to produce non spherical objects. For example a very interesting study by Cheng et al showed the possibility to self assemble rod-coil polyethylenimine-poly(ethylene glycol)-␣-cyclodextrin inclusion complexes into hollow spheres and rod-like particles (Cheng et al, 2011). Alternatively, polypeptides copolymers are known to self-associate and form various aggregate structures (Cai et al, 2011), ranging from spheres to worms and very elongated fibers and other structures.…”
Section: Introductionmentioning
confidence: 98%